Mobility of copper and zinc fractions in fungicide-amended vineyard sandy soils - Brunetto G. (2014)
The purpose of this study was to evaluate the mobility of copper (Cu) and zinc (Zn) in the profile and distribution of sandy soil fractions from vineyards. Soil samples were collected from two vineyards of different ages (14 and 30 years) and a natural field area in the south of Brazil. The chemical characteristics, Cu levels and Zn levels, were analyzed in the soils by extraction with ethylenediamine tetraacetic acid (EDTA) using the 3050B method of USEPA and by chemical fractionation. Cu and Zn were accumulated in the vineyard soils, especially in the uppermost soil layers and in the soil from the oldest vineyard. Approximately, 75% of the total Cu was extracted by EDTA, but only 30% of the total Zn was extracted by EDTA. Most of the Cu, especially in the oldest vineyard, was distributed in the mineral-associated fraction, which is characterized by low geochemical mobility, but another important part of the Cu was distributed in the soil organic matter. Most of the Zn in the soil was distributed in the residual and mineral-associated fractions, which are characterized by low mobility and have potential for causing toxicity to plants. © 2013 © Taylor & Francis.